A new health check of the ozone layer at global and regional scales. Issue 12 (19th June 2014) - Coldewey‐Egbers, Melanie; Loyola R., Diego G.; Braesicke, Peter; Dameris, Martin; van Roozendael, Michel; Lerot, Christophe; Zimmer, Walter
Abstract In this study, we provide a new perspective on the current state of the ozone layer using a comprehensive long‐term total ozone data record which has been recently released within the framework of the European Space Agency's Climate Change Initiative. Based on a multivariate regression analysis, we disentangle various aspects of ozone change and variability on global and regional scales, thus enabling the monitoring of the effectiveness of the Montreal Protocol. Given dominant natural variability the expected midlatitude onset of ozone recovery is still not significant and would need additional 5 years of observations to be unequivocally detectable. A regional increase in the tropics is a likely manifestation of a long‐term change in El Niño–Southern Oscillation intensity over the last two decades induced by strong El Niño in 1997/1998 and strong La Niña in 2010/2011.